2014
DOI: 10.3390/rs6021538
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Crop Injury from Glyphosate on Soybean and Cotton Using Plant Leaf Hyperspectral Data

Abstract: Abstract:In this paper, we aim to detect crop injury from glyphosate, a herbicide, by both traditionally used spectral indices and newly extracted features with leaf hyperspectral reflectance data for non-Glyphosate-Resistant (non-GR) soybean and non-GR cotton. The new features were extracted by canonical analysis technique, which could provide the largest separability to distinguish the injured leaves from the healthy ones. Spectral bands used for constructing these new features were selected based on the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 42 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…All simulated fluorescence spectra combined with the corresponding selected values of input parameters were used as input data for the sensitivity analysis. Detailed procedure and formulae can be found in our previous studies [21,22].…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…All simulated fluorescence spectra combined with the corresponding selected values of input parameters were used as input data for the sensitivity analysis. Detailed procedure and formulae can be found in our previous studies [21,22].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…In the first step, the leaf structure parameter N was firstly inverted from the measured data of leaf reflectance (ρleaf) and transmittance (τleaf) by minimizing the following merit function Fn(N), which is defined in the near-infrared wavelengths (λ) of 750-1300 where N is the most sensitive parameter among the input parameters of the PROSPECT-5 model [22] …”
Section: Inversion Proceduresmentioning
confidence: 99%
“…Leaf apparent reflectance spectra were acquired by using an ASD integrating sphere apparatus coupled with an ASD FieldSpec 3 Hi-Res spectroradiometer (ASD Inc., Boulder, CO., USA), according to the procedure described by Zhao et al [5,21]. Four ChlF-related spectral indices were calculated from the leaf apparent reflectance spectra.…”
Section: Calculation Of Chlf-related Spectral Indicesmentioning
confidence: 99%
“…Many studies have been reported which analyzed the effectiveness of employing reflectance-based spectral indices and transformed spectral features in detecting glyphosate injury [5]. However, these methods have suffered from two main drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The SCOPE model includes leaf, canopy, soil, and meteorology variables as inputs. By using the method of global sensitivity analysis given by Zhao et al [22], the sensitivity indices of the input parameters of the SCOPE model (Version 1.51) were calculated (not shown). Results revealed that, among all the 58 input parameters, 15 of them have considerable impact on the simulated Fs spectra.…”
Section: Simulated Datamentioning
confidence: 99%